Clinico-epidemiological profile of patients with traumatic anserine folliculosis: A retrospective study from a tertiary care center in North India - Ramesh Kumar; Arti Singh; Rozy Badyal; Suresh Kumar Jain; Devendra Yadav (Wolters Kluwer Medknow Publications, 2020)
Background: Traumatic anserine folliculosis (TAF) is an uncommon follicular dermatosis. It is characterized by multiple closely set grouped follicular papules with goose skin appearance. There are few publications about this condition, and little is known about the incidence and peak age and sex groups. Aims and Objectives: The aim of this study is to describe the various pattern of TAF in children of 6 years to 18 years of age group. Methods: A retrospective study was conducted to identify cases of TAF in 26 patients at the dermatology department of our tertiary care hospital. The study population was 6-18 years age group children. History, variables, cutaneous and systemic examination, and routine laboratory investigations data were collected from previously recorded forms. Results: Twenty-six patients with TAF were identified. Of these, 19 were male and 7 were female. The mean age was 12.11 ± 2.2 years, ranging from 8 to 16 years. Only four patients were older than 14 years. The mean duration of lesions was 10.23 ± 7.2 months. We classified the clinical patterns as mental, mandibular, and malar according to anatomic location. The most common lesion locations were the chin in 20 (76.7%) followed by the body of mandible in 4 (15.38%) and cheek in 2 (7.69%) cases. Friction and pressure were the predisposing factors in most of the cases. Conclusion: The most commonly affected age group was 8-14 years in 22 (84.6%) children, and the most common predisposing factors were friction and pressure. Therefore, early diagnosis with proper counseling and lifestyle modification of TAF provides rapid relief for patients and avoid unnecessary tests and treatments.